Double-humped strain hardening in a metastable ferrous medium-entropy alloy by cryogenic pre-straining and subsequent heat treatment. (1st April 2022) - Lee, Jungwan; Bae, Jae Wung; Asghari-Rad, Peyman; Kim, Hyoung Seop
Abstract: Significant benefits of either heterogeneous microstructures or deformation-induced martensitic transformation (DIMT) in metallic materials stem from their superior strain hardening and tensile properties. Herein, we present an unprecedented strain hardening behavior at 77 K in a ferrous medium-entropy alloy comprising a metastable face-centered cubic (FCC) bimodal microstructure with different grain sizes. Pre-straining yields fine body-centered cubic (BCC) martensites, and subsequent heat treatment causes reverse martensitic transformation from BCC to FCC, affording the bimodal FCC microstructure. Furthermore, the yield strength is enhanced due to the presence of submicron FCC grains and geometrically necessary dislocations (GNDs) that are generated during the pre-straining. Profuse GNDs in reversely transformed FCC promote DIMT. Moreover, when true strain exceeds 0.2, widespread DIMT in the interior of the remaining FCC drastically increases the strain hardening rate and consequently delays necking. The outstanding tensile properties derived from this thermomechanical process are because of the DIMT and hetero-deformation-induced strengthening. Graphical abstract: Image, graphical abstract